Juvenile age estimation from facial images. Issue 1 (January 2017) - Ferguson, Eilidh; Wilkinson, Caroline
Abstract: Age determination from images can be of vital importance, particularly in cases involving suspected child sexual abuse (CSA). It is imperative to determine if an individual depicted in such an image is indeed a child, with a more concise age often sought, as this may affect the severity of offender sentencing. The aims of this study were to establish the accuracy of visual age estimation of the juvenile face in children aged between 0 and 16 years and to determine if varying levels of exposure to children affected an individual's ability to assess age from the face. An online questionnaire consisting of 30 juvenile face images was created using SurveyMonkey®. The overall results suggested poor accuracy for visual age estimation of juvenile faces. The age, sex, occupation and number of children of the participants did not affect the ability to estimate age from facial images. Similarly, the sex and age of the juvenile faces did not appear to affect the accuracy of age estimation. When specific age groups are considered, sex may have an influence on age estimation, with female faces being aged more accurately in the younger age groups and male faces more accurate after the age of 11 years, however this is based on a small sample. This study suggests that the accuracy of juvenile age estimation from the face alone is poor using simple visual assessment of images. Further research is required to determine exactly how age is assessed from a facial image, if there are indicators, or features in particular that lead to over- or under-estimation of juvenile age. Highlights: Visual age estimation of children's faces reveals poor accuracy at 33%. Participants with children do not achieve higher results in facial age estimation. Individuals working with children also show low accuracy of age assessment. Age estimation accuracy appears to vary for male and female faces across age groups.